Clinical aspects, differential diagnosis and treatment of young people with Attention Déficit Hyperactivity Disorder (ADHD) (Research, Society and Development, 2023)
Introduction: The Attention Deficit Hyperactivity Disorder (ADHD) is a neurological condition that impairs focus or attention, it is a pathology frequently diagnosed in childhood, however, it is not identified until adolescence. Generally, there is a genetic component in the pathophysiology of ADHD, however, there are other causes that are not yet well established. Objective: To analyze clinical aspects and the treatment indicated for young people diagnosed with Attention Deficit Hyperactivity Disorder (ADHD). Methodology: This is a narrative review of the literature, with articles selected from the databases: National Library of Medicine (PubMed MEDLINE), EbscoHost, Google Scholar, Scientific Eletronic Library Online (SCIELO) and Virtual Health Library (BVS) Results: According to the review conducted, it was found that ADHD is composed of two groups of symptoms: inattention and hyperactivity-impulsivity. In addition, inattention and impulsivity problems are characteristics that parents often ignore, contributing to a late diagnosis. Furthermore, adolescents and adults have less hyperactivity than children; however, there is a significant deficit in executive functions, which may compromise their intellectual development. Conclusion: We can state that ADHD symptoms vary according to gender, age, and type of Attention Deficit Hyperactivity Disorder. Therefore, a prior diagnosis is of utmost importance for the young ADHD sufferer to have a good quality of life, as provided by the World Health Organization.